Development of Physical Training Model in Futsal Games Based on Circuit Training in Senior High Schools in Palembang City - Yangkara, Yosef Ferdy; Fikri, Aprizal; Satria, M. Haris; Septaliza, Dewi; Hidayat, Arif; Victorian, Achmad Richard; Suwardoyo, Yoyok (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
Physical training is a mandatory exercise for an athlete to perform optimally during the competition and so that the athlete can display the techniques that have been learned and can apply the tactics given by the coach because without a good physique an athlete cannot do everything that has been explained. The purpose of this study is to produce a physical training model for futsal games. The method used in this study is the ADDIE analysis, design, development, implementation, and evaluation method. The results of this study were obtained from expert validation that had been carried out involving three experts including one futsal coach, one futsal academic and one futsal practitioner. The instrument in this study used a questionnaire. Based on the results of the CVI and CVR analysis which obtained a value of 0.5 or valid. It can be interpreted that the YAF 1 model is feasible to be used and applied to the physical training of extracurricular high school students in the city of Palembang